2010
DOI: 10.1007/s11356-010-0390-3
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine disrupting potential of sediments from the Upper Danube River (Germany) as revealed by in vitro bioassays and chemical analysis

Abstract: Of the nine sediment extracts tested five extracts exhibited significant estrogenic activities in the YES, which suggested the presence of ER agonists in these samples. The xenoestrogens nonylphenol (NP) and bisphenol A (BPA) and the natural estrogen estrone (E1) were detected while concentrations of 17β-estradiol (E2) and ethinylestradiol (EE2) were less than their respective limits of quantification in all sediment extracts. A comparison of the measured YES-EEQs and the calculated Chem-EEQs revealed that as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 107 publications
1
42
1
Order By: Relevance
“…The E2 EQs of the samples that revealed a positive receptor-mediated response were between 0.3 and 1.0 ng E2 EQ g −1 dw. These values are comparable to YES E2 EQs reported by other studies, including sediments collected from the UK rivers with 0.20-13 ng E2 EQ g −1 dw (Thomas et al 2004) and German rivers with 0.03-1.3 ng E2 EQ g −1 dw (Grund et al 2011), as well as the values of sediment analysis from Dutch inland and estuarine waters ranging from 0.10 to 1.2 ng E2 EQ g −1 dw (Legler et al 2002) and from Chinese Liao River with non-detectable to 6.04 ng E2 EQ g −1 dw ). On the other hand, sediment YES-E2 EQs reported in our present study are much greater than those reported in other studies, including sediments from the UK estuaries with 0.021-0.03 ng E2 EQ g −1 SEQ (Peck et al 2004), from Dutch inland and estuarine waters with 0.005 and 0.34 ng E2 EQ g −1 SEQ (Houtman et al 2006), and sediment from a Korean lake with E2 EQs ranging from 0.003 to 0.064 ng E2 EQ g −1 dw (Koh and Khim 2005).…”
Section: Er Agonist Potencies Of Sediment Extractssupporting
confidence: 88%
“…The E2 EQs of the samples that revealed a positive receptor-mediated response were between 0.3 and 1.0 ng E2 EQ g −1 dw. These values are comparable to YES E2 EQs reported by other studies, including sediments collected from the UK rivers with 0.20-13 ng E2 EQ g −1 dw (Thomas et al 2004) and German rivers with 0.03-1.3 ng E2 EQ g −1 dw (Grund et al 2011), as well as the values of sediment analysis from Dutch inland and estuarine waters ranging from 0.10 to 1.2 ng E2 EQ g −1 dw (Legler et al 2002) and from Chinese Liao River with non-detectable to 6.04 ng E2 EQ g −1 dw ). On the other hand, sediment YES-E2 EQs reported in our present study are much greater than those reported in other studies, including sediments from the UK estuaries with 0.021-0.03 ng E2 EQ g −1 SEQ (Peck et al 2004), from Dutch inland and estuarine waters with 0.005 and 0.34 ng E2 EQ g −1 SEQ (Houtman et al 2006), and sediment from a Korean lake with E2 EQs ranging from 0.003 to 0.064 ng E2 EQ g −1 dw (Koh and Khim 2005).…”
Section: Er Agonist Potencies Of Sediment Extractssupporting
confidence: 88%
“…A combination of the triad approach with together with EDA is a promising conceptual framework to overcome this shortcoming (Chapman and Hollert 2006) these include the potential of chemicals to interact with the nuclear sex hormone receptors (estrogen and androgen receptor) or to affect the synthesis of steroid hormones. Recent studies have demonstrated, however, that some of these assays such as the L-YES (Wagner and Oehlmann 2009) and the H295R Steroidogenesis Assay (Gracia et al 2008;Grund et al 2009;Hecker et al 2007;Hecker and Giesy 2008) have very great promise as biotests in support of EDA of complex environmental samples. Initial studies with sediments and sewage treatment plant effluents have revealed differential effects when using a combination of different bioassays that capture estrogenic, steroidogenic, dioxin-like, mutagenic/genotoxic and teratogenic effects, fractionation, and chemical analysis, demonstrating the necessity of holistic screening approaches.…”
Section: Effect Directed Analysesmentioning
confidence: 99%
“…A number of studies have been conducted to characterize the endocrine potential of municipal effluents [24,25], surface water [26][27][28] and sediments [26,27,29,30], and there has been increasing awareness of the need for testing approaches targeting EDCs to be included into current environmental assessments and monitoring [31][32][33][34][35][36] …”
Section: Environmental Sources and Exposure To Edcsmentioning
confidence: 99%
“…For example, Kidd et al [7] demonstrated declines in populations of certain fish species after exposure to environmentally relevant concentrations of the synthetic estrogen ethinylestradiol in whole lake experiments. Additionally, various studies demonstrated the potential of sediment-bound EDCs to cause adverse effects in aquatic wildlife using different in vitro and in vivo assays [26,27,29,30,[37][38][39]. Recent studies predicted that the objective of the WFD to achieve good ecological/chemical status by 2015 is likely to fail in many European catchment areas because of the continuing remobilization of sedimentbound pollutants in heavily contaminated old sediments [40][41][42].…”
Section: Levelmentioning
confidence: 99%